State Regulatory Policy in Development of Non-Waste Production in the Agro-Industrial Complex (Economics and region, 2018)
The article deals with the problem of state regulation of the non-waste production in the agro-industrial complex. The necessity of providing an effective state regulatory policy with non-waste agricultural production to overcome the crisis phenomena in waste management in the agro-industrial complex and ensuring the further intensive development of agro-industrial production has been substantiated. The main directions of realization of the state policy in non-waste production in the agro-industrial complex have been determined: to identify reserves of resource conservation through the use of AIC waste and maximally possible to use their resource potential; to improve the organization of harvesting, storage, transportation and use of agricultural waste as a secondary raw material; to intensify the stimulation of the development of non-waste technological systems in the agro-industrial complex through the implementation of state budget support programs for the establishment of such systems; to create favorable conditions for the organization of non-waste industries at enterprises of Ukraine, taking into account leading foreign experience; to increase the efficiency of the system of engineering and technical maintenance of non-waste agricultural production, in particular, through the improvement of its organization and management; to improve the accounting and reporting systems of the waste from agro-industrial complex; to implement the preventive measures for uncontrolled export of agricultural waste; to form a secondary resource base in the secondary resources market; to introduce the practice of periodic review of technology of agro-industrial production. It has been proved that ensuring a proper state regulation in non-waste agricultural production and creation of the appropriate organizational and economic conditions is an important step in solving a complex of economic, ecological, and social problems of sustainable development of Ukraine.
Keywords: non-waste technologies; non-waste agricultural production; agro-industrial complex; state regulation